Development of a force field with condensed phase consistent charges for N,N' - dialkylimidazolium room temperature ionic liquids - Mngadi, Vela (Department of Chemistry, 2016)
Most force field models for Room temperature ionic liquids cannot properly elucidate statics and dynamics. It is in this context that we set to assess the most efficient way to model RTILs while maintaining the integrity of the liquids statics and dynamics. The development approach begins with the investigation of the effects that the linear scaling of partial atomic charges on nonpolarisable force fields from a reference potential has on the structure and dynamics of the room temperature ionic liquids (RTILs) 1-butyl-3-methylimidazolium tetraflouroborate [C4MIM][BF4] and 1-butyl-3-methylimidazolium hexaflourophosphate [C4MIM][PF6]. The results show that the three-dimensional structure of the liquid is changed ever so slighter by the linear scaling of atomic charges. While dynamic properties such as viscosity and self-diffusion coefficients were majorly affected by charge scaling. Self-diffusion coefficients that span a range of four orders of magnitude between the original model and the scaled model where the ionic charge was ±0.6 e. Viscosity estimates calculated using the Green-Kubo and the Einstein relationships revealed that the linear scaling of atomic charges results in increased mobility of the simulated liquid. Implicit inclusion of polarisation effects was investigated, Here a new charge scheme development using Quantum mechanics/Molecular mechanics (QM/MM) methods in CHARMM 35 interfaced with GAMESS-UK was propose. The atomic charges were derived from liquid phase calculations using an iterative procedure. This was carried out for individual ions and cation-anion pairs, for the analysis of charge transfer, within the liquid environment. The results obtained gave predictions of density, liquid structure and self-diffusion coefficients that were in excellent agreement with experimental data available. This method is preferable over the commonly used charge scaling methodology which is deem as an unphysical approach for the simulation of [C4MIM][BF4] and [C4MIM][PF6]. A polarisable force field based on the Drude oscillator model is presented. The model proves to be most effective for the simulation of RTILs. The force field accurately reproduced experimental results for the physicochemical properties reviewed.